STABILITAS KEUANGAN BPR DI KOTA SURABAYA DENGAN PROFITABILITAS BANK SEBAGAI VARIABEL MODERASI - Evi Sistiyarini; Agustina Ratna Dwiati (LPPM Politeknik Pratama, 2025)
Financial stability in Rural Credit Banks (BPR) is very important because BPR as an intermediary institution can support the regional economy and help SMEs in carrying out business activities. Banks that have good financial stability will have an impact on customer trust, support economic resilience, prevent systemic risk and reduce the risks faced by the bank. The independent variables used are LDR, cash ratio, NPL, and BOPO. The moderating variable used is ROA. The dependent variable is bank's financial stability (Z score). The research sample consisted of 14 Rural Credit Banks (BPR) which were taken using the purposive sampling method in the first quarter of 2021 to the fourth quarter of 2023. The panel data regression method and Moderated Regression Analysis were processed using the eviews program. The results of the study showed that partially the LDR and BOPO variable has a negative but insignificant effect on financial stability in BPR in Surabaya City. The cash ratio and NPL variables have a positive and significant effect on financial stability in BPR in Surabaya City. ROA as a moderating variable is able to significantly moderate the influence of LDR, cash ratio and NPL on the financial stability of BPRs in Surabaya City.